Local perceptions on the impact of drought on wetland ecosystem services and associated household livelihood benefits: The Case of the Driefontein Ramsar site in Zimbabwe - Marambanyika, Thomas; Mupfiga, Upenyu Naume; Musasa, Tatenda; Ngwenya, Keto (MDPI, 2022)
The paper assesses local people’s perceptions on the impact of drought on wetland ecosystem services and the associated household livelihood benefits, focusing on the Driefontein Ramsar site in Chirumanzu district, Zimbabwe. Field data were obtained using a questionnaire from 159 randomly selected households, key informant interviews and transect walks. The study findings show that provisioning, regulating and supporting services are severely affected by a high frequency of drought, occurring at least once every two years, compared to cultural services. There is a reduction in water for domestic use and crop farming, pasture for livestock, fish, thatch grass and ground water recharge. Although cultural services such as traditional rain-making ceremonies and spiritual enhancement are largely unaffected by drought, the wetland’s aesthetic value was reported to be diminishing. The habitat and breeding areas of endangered crane bird species were perceived to be dwindling, affecting their reproduction. All the household heads are not formally employed and largely depend on the wetland resources for food and income. However, drought is adversely affecting wetland-based agricultural activities that are key pillars of the households’ economy. Therefore, there is a need for alternative livelihood strategies that enable local communities to adapt to drought impacts without exerting more pressure on the declining wetland resources.